Impact of novel oral anticoagulants vs warfarin on effusions after coronary artery bypass grafting. Issue 6 (23rd April 2019) - Yu, Pey‐Jen; Lin, Dishen; Catalano, Michael; Cassiere, Hugh; Manetta, Frank; Kohn, Nina; Hartman, Alan
Abstract: Background: Novel oral anticoagulants (NOAC) have been shown to have comparable risk profiles compared with warfarin. However, data on the use of NOACs in cardiac surgery patients is limited. The aim of this study is to compare postoperative effusion rates in patients who were anticoagulated with NOACs vs warfarin after coronary artery bypass grafting (CABG). Methods: A retrospective review of 2017 patients undergoing isolated CABG from 2014 to 2017 was performed. Of those patients, 246 patients (12.2%) were placed on either a NOAC or warfarin postoperatively. The combined rates of postoperative pericardial and pleural effusions requiring invasive intervention during the index hospitalization and up to 3 months postoperatively were compared between patients who were placed on NOACs vs warfarin. Results: Of the 246 patients placed on oral anticoagulation after isolated CABG, 64 (26.0%) were placed on NOACs, and 182 (74.0%) received warfarin. There were no significant differences in preoperative coagulation profile and use of anticoagulation and antiplatelets preoperatively between the groups. Of the patients anticoagulated with NOACs postoperatively, 17 patients (26.6%) required invasive interventions for effusions compared with 24 patients (13.2%) in the cohort anticoagulated with warfarin ( P < 0.014). Of the patients who required interventions for effusions, those on NOACs were more likely to require delayed interventions compared with those on warfarin. Conclusions: Patients receiving NOACs after CABG are at increased risk of developing effusions requiring invasive interventions compared to patients receiving warfarin. This increased risk should be taken into consideration when choosing the appropriate anticoagulation strategy for postoperative patients with CABG.